God's lunatics : lost souls, false prophets, martyred saints, murderous cults, demonic nuns, and other victims of man's eternal search for the divine - Largo, Michael, 1954- (New York : Harper, 2010)
What is the meaning of life? Since the dawn of civilization, humankind has sought to answer the mysteries of existence. Unfortunately this restless search for the divine has, all too often, driven seekers in regrettable directions-- toward the comically ridiculous and irrational but also the frighteningly horrific and maniacal.
Includes bibliographical references (p. [537]-556).
Keywords: Prophets -- History; Religious leaders -- History; Religious life -- Encyclopedias; Religions -- Encyclopedias